Cooperation between Russia and Kazakhstan as a Vector of Eurasian Integration - Yu. A. Davydova; E. V. Kargapolova (Евразийская интеграция: экономика, право, политика, 2022)
The study analyzes the areas of cooperation between Russia and Kazakhstan within the framework of Eurasian integration.Aim. To identify the presence of factors contributing to the strengthening of relations between Russia and Kazakhstan at the present stage and obstacles hindering the deepening of integration processes.Tasks. To analyze the current state of cooperation between the two countries within the framework of the Eurasian Union, to identify obstacles to deepening integration processes, to show forecast scenarios of interaction between Russia and Kazakhstan. To analyze how these scenarios will affect the relationship between the two countries, and what consequences will be if each of them is implemented.Methods. The article uses general scientific methods of analysis and synthesis, a systematic approach, as well as an empirical method of expert evaluation.Results. The study showed that there are strong relations between the two countries in the economic sphere within the framework of the EAEU. Russia is the main trading partner of Kazakhstan. Projects related to the Caspian Sea are being developed and look very promising. Joint military exercises and supplies of Russian weapons are of great interest to Kazakhstan. Russia acts as a guarantor of Kazakhstan’s security in the region and its main partner in the Eurasian space. The Collective Security Treaty Organization also plays an important role in the relations between the two countries, which proved its effectiveness in the January 2022 events, contributing to the resolution of the political crisis and preventing extremist actions of armed terrorist groups. At the same time, the role of Kazakhstan as its closest neighbor and ally is also important for Russia, especially in the context of escalating international tensions.Conclusions. Both Russia and Kazakhstan are interested in further cooperation in the economic, military and cultural spheres. At the same time, the further deepening of integration processes is hindered by the absence of large joint investment projects and the multi-vector nature of Kazakhstan’s foreign policy. In the context of the information war of the West against Russia and the increasing international tension, it is extremely important to deepen cooperation between the two countries.